Topics and political frameworks for the news of the Iraqi Ministry of Foreign Affairs on its website: an analytical study - Al-Rubaye, Taha Ali; Murad, Kamel Khurshid (ALBAHITH ALALAMI, 2022)
This is a descriptive study that used the survey method, it’s aimed to identify the topics and frameworks of diplomatic and political issues covered by the news of the website of the Iraqi Ministry of Foreign Affairs, through the content analysis method applied on a sample selected in a systematic random manner for news published in the year 2021. The sample included (191) news equivalent to (20%) of the total study population of (942). The study reached some results, the most important of which were as follows: The political issue, in its general sense, grabbed the most prominent attention among the various issues and events focused on by Iraqi diplomacy: "international cooperation", "bilateral cooperation", and then "regional political coordination" appeared as the most prominent political issues. Also, The frameworks of “general bilateral relations” and “political diplomatic cooperation” were dominant in the news. The frameworks of “regional cooperation,” economic cooperation,” “international cooperation,” and “security/military cooperation” appeared as frameworks for diplomatic and political activity. This reflects the interests of the Iraqi diplomacy in strengthening Iraq's relations with the various active powers in the world.